The susceptibility of cochlear outer hair cells to cyclodextrin is not related to their electromotile activity - Zhou, Yingjie (Acta Neuropathol Commun, 2018)
Niemann-Pick Type C1 (NPC1) disease is a fatal neurovisceral disorder caused by dysfunction of NPC1 protein, which plays a role in intracellular cholesterol trafficking. The cholesterol-chelating agent, 2-hydroxypropyl-β-cyclodextrin (HPβCD), is currently undergoing clinical trials for treatment of this disease. Though promising in alleviating neurological symptoms, HPβCD causes irreversible hearing loss in NPC1 patients and outer hair cell (OHC) death in animal models. We recently found that HPβCD-induced OHC death can be significantly alleviated in a mouse model lacking prestin, an OHC-specific motor protein required for the high sensitivity and sharp frequency selectivity of mammalian hearing. Since cholesterol status is known to influence prestin’s electromotility, we examined how prestin contributes to HPβCD-induced OHC death in the disease context using the NPC1 knockout (KO) mouse model (NPC1-KO). We found normal expression and localization of prestin in NPC1-KO OHCs. Whole-cell patch-clamp recordings revealed a significant depolarization of the voltage-operating point of prestin in NPC1-KO mice, suggesting reduced levels of cholesterol in the lateral membrane of OHCs that lack NPC1. OHC loss and elevated thresholds were found for high frequency regions in NPC1-KO mice, whose OHCs retained their sensitivity to HPβCD. To investigate whether prestin’s electromotile function contributes to HPβCD-induced OHC death, the prestin inhibitor salicylate was co-administered with HPβCD to WT and NPC1-KO mice. Neither oral nor intraperitoneal administration of salicylate mitigated HPβCD-induced OHC loss. To further determine the contribution of prestin’s electromotile function, a mouse model expressing a virtually nonelectromotile prestin protein (499-prestin) was subjected to HPβCD treatment. 499-prestin knockin mice showed no resistance to HPβCD-induced OHC loss. As 499-prestin maintains its ability to bind cholesterol, our data imply that HPβCD-induced OHC death is ascribed to the structural role of prestin in maintaining the OHC’s lateral membrane, rather than its motor function. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40478-018-0599-9) contains supplementary material, which is available to authorized users.